Pendampingan Proses Pengadaan Barang Produksi dari Supplier Lokal dan Internasional di PT Sunningdale Tech Batam - Manda Carissa; Wisnu Yuwono (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
This internship program was carried out at PT Sunningdale Tech Batam with a focus on assisting and analyzing the material procurement process from both local and international suppliers, which has been affected by various challenges such as resin import quota regulations, slow customs clearance processes, and external disruptions including extreme weather and geopolitical conflicts. Through direct observation, interviews, and the collection of procurement administrative documents, this activity successfully mapped the entire procurement flow and identified key obstacles that cause material delays. The output produced is an official procurement flowchart that was then implemented across three departments, demonstrating improved process effectiveness through reduced lead time for local materials from 7–9 days to 6–8 days and for imported materials from 21–25 days to 18–22 days, along with fewer documentation errors and increased staff understanding of procedural workflows. Overall, this internship activity provides a significant contribution to the company by enhancing procurement efficiency, strengthening cross-departmental coordination, and improving supply chain resilience against external risks.